2013
DOI: 10.2217/cer.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of antiarrhythmic drugs on cardiovascular hospitalization and mortality in atrial fibrillation

Abstract: Assessment of the comparative effectiveness of individual AADs on CV hospitalization and mortality end points is not possible with the current evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Important patient subgroups, including the elderly, and those with coexisting morbidities, are frequently under-represented in clinical trials of cardiovascular drugs [12, 13]. Likewise, AF clinical trial populations vary in their representativeness to real-world AF patients [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Important patient subgroups, including the elderly, and those with coexisting morbidities, are frequently under-represented in clinical trials of cardiovascular drugs [12, 13]. Likewise, AF clinical trial populations vary in their representativeness to real-world AF patients [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…21 Reported event rates for stroke, heart failure, and mortality are low; however, the potential benefits of AAD in reducing these events are yet to be established. 2,21,24 The Impact of Antiarrhythmic Drug Therapy on Patients AAD therapy is effective at reducing AF recurrences, 21 controlling symptoms of AF, and improving patient QoL. 25 In the A4 study, paroxysmal AF patients (N=112) treated with AAD showed a 13% reduction in symptom frequency (p=0.002) and a 38% reduction in symptom severity (p<0.0001) as measured by the AF Symptom Frequency and Severity Checklist.…”
Section: Clinical Impact Of Antiarrhythmic Drug Therapymentioning
confidence: 99%